Research of the physical and chemical properties of diatomite as a carrier of phase change materials for use in advanced building materials - Przybek, Agnieszka; Łach, Michał; Hebdowska-Krupa, Maria; Miernik, Krzysztof; Mikuła, Janusz (Frontiers in Materials, 2024)
Diatomaceous earth (diatomite) is a material that exhibits unique properties that can be used in many areas of the economy. The use of diatomite as a sorbent for absorbing oil substances has been known for many years. Diatomite, thanks to its structure, acts like a sponge, absorbing oil substances. Its micropores increase the surface area in contact with the pollutant, which speeds up the absorption process. Diatomite is used to clean up oil spills on land and water, secure industrial sites, treat wastewater, and manage pollution at ports and oil ports. Many scientific papers to date have focused on evaluating the potential of diatomite as a medium for petroleum substances. Still, there is little mention of the potential for using diatomite as a carrier for paraffinic PCMs. Paraffins are synthetic compounds obtained by distillation from a specific fraction of crude oil. This paper presents a study of the physicochemical properties of diatomite with a view to its subsequent use as a medium for absorbing paraffinic phase change materials. Thanks to its high porosity, high specific surface area, low density, and chemical inertness, this material is an ideal medium for paraffinic substances. In addition, its most important feature is the absence of desorption. A new type of environmentally friendly and cheap phase change materials may contribute to the increase in the use of this type of materials in construction. The benefits of using PCM materials are known.